First do no harm: infectious deaths in pediatric ALL - Rabin, Karen R. (American Society of Hematology, 2014)
In this issue of Blood, O’Connor and colleagues describe infection-related mortality on the United Kingdom Childhood Acute Lymphoblastic Leukaemia Randomised Trial 2003 (UKALL 2003) for children with newly diagnosed acute lymphoblastic leukemia, reporting a 5-year cumulative incidence of 2.4%, with Down syndrome (DS) being the factor most predictive of increased risk.(1)